شعرية التناص في شعر رمضان بونكانو ترانيم كعبي يتكئ على التوباد أنموذجا - زايد, عجيبة, أبو سليمان حسن (Univercty of Eloued, 2020)
تطرّقنا من خلال هذه المذكرة إلى ذكر بعض جوانب التناص، فالتناص متعدد الأشكال، وتبقى الدّراسة مفتوحة من عدّة جوانب لدى الدّارسين على اختلاف مشاربهم ، واتجاهاتهم الفكريّة والأدبيّة.Through this memo, we touched upon mentioning some aspects of intertextuality, as intertextuality is polymorphic, and the study remains open from many aspects to scholars of all backgrounds, intellectual and literary trends.
Keywords: – شعر رمضان بونكانو– الاتجاهات الفكرية والأدبية التناص; Intertextuality - Ramadan Buncano Poetry - Intellectual and Literary Trends